Estimation of Sex From Dental Arch Dimensions: An Odontometric Analysis. Issue 8 (November 2021) - Kanchan, Tanuj; Chugh, Vinay; Chugh, Ankita; Setia, Puneet; Shedge, Rutwik; Krishan, Kewal
Abstract : Abstract: Sex estimation is one of the "big three" of human identification and is a vital aspect of the process of generating biological profile of unknown deceased. Anthropometric and odontometric methods that utilize measurement of distances between certain landmarks are commonly employed to differentiate between the 2 sexes. Teeth are the most robust and well-preserved parts of the human body, and studies have shown that the sex of an unknown individual can be estimated using their measurements. The present study was carried out to analyze the sex differences based on the dental arch dimensions of both the jaws in an Indian population. A proper understanding of dental arch dimensions not only help forensic odontologists in human identification, but also help dental practitioners in teeth restoration, and to quantify selection of anterior teeth in bonding of dentures. The dental arch dimensions of the canines, premolars, and the molars of both the jaws were recorded in dental casts of 307 participants. Comparison of the dental arch dimensions of males and females was done and logistic regression models were generated to estimate sex. Receiver Operating Characteristic analysis was done to find out the potential to estimate sex for all the dental arch dimensions in both the sexes. It was observed that maxillary intermolar II distance gave the best results in estimating the sex. The sexing accuracy is seen to increase as we go distally from canines to molars in each jaw; minimum for intercanine distance and maximum for distance between the 2nd molars. The sexing accuracy from dental arch dimensions was found to be between 72.7% and 86.5%. The models derived for estimation of sex from dental arch dimensions can be used in cases of skeletal remains. Abstract : Supplemental Digital Content is available in the text